Inter-subject Correlation While Listening to Minimalist Music: A Study of Electrophysiological and Behavioral Responses to Steve Reich's Piano Phase - Dauer, Tysen; Nguyen, Duc T.; Gang, Nick; Dmochowski, Jacek P.; Berger, Jonathan; Kaneshiro, Blair (Frontiers in Neuroscience, 2021)
Musical minimalism utilizes the temporal manipulation of restricted collections of rhythmic, melodic, and/or harmonic materials. One example, Steve Reich’s Piano Phase, offers listeners readily audible formal structures containing unpredictable events at local levels. Pattern recurrences may generate strong expectations which are violated by small temporal and pitch deviations. A hyper-detailed listening strategy prompted by these minute deviations stands in contrast to the type of listening engagement typically cultivated around functional tonal Western music. Recent research has suggested that the inter-subject correlation (ISC) of electroencephalographic (EEG) responses to natural audio-visual stimuli objectively indexes a state of "engagement", demonstrating the potential of this approach for analyzing music listening. But can ISCs capture engagement with minimal music, which features less obvious expectation formation and has historically received a wide range of reactions? To approach this question, we collected EEG and continuous behavioral (CB) data while 30 adults listened to an excerpt from Steve Reich’s Piano Phase, as well as three controlled manipulations and a popular-music remix of the work. Our analyses reveal that EEG and CB ISC are highest for the remix stimulus and lowest for our most repetitive manipulation. In addition, we found no statistical differences in overall EEG ISC between our most musically meaningful manipulations and Reich’s original piece. We also found that aesthetic evaluations corresponded well with overall EEG ISC. Finally we highlight co-occurrences between stimulus events and time-resolved EEG and CB ISC. We offer the CB paradigm as a useful analysis measure and note the value of minimalist compositions as a limit case for studying music listening using EEG ISC. We show that ISC is less effective at measuring engagement with this minimalist stimulus than with popular music genres and argue that this may be due to a difference between the type of engagement measured by ISC and the particular engagement patterns associated with minimalism.